2022
DOI: 10.1088/1755-1315/961/1/012054
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Attapulgite as Internal Curing in High-Performance Concrete with Variable Temperature Curing to Enhance Mechanical Properties

Abstract: One of the most important elements in the development of compressive strength is concrete curing, and a large temperature differential during curing may decrease strength. This exudation is caused by microcracks in the concrete caused by the continuous temperature fluctuation. By minimizing autogenous shrinkage, internal curing has become popular for reducing the danger of early-age cracking in high-performance concrete (HPC). The efficacy of internal wet curing provided by fine Attapulgite aggregate is invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Aconite is abundant and cheap, it can be modified by calcination and other methods and promote the early hydration reaction [21,22], improving the effect of the early mechanical properties of cementitious materials. palygorskite is mostly used in the construction field [23][24][25][26], but little research has been reported in the filling field.…”
Section: Introductionmentioning
confidence: 99%
“…Aconite is abundant and cheap, it can be modified by calcination and other methods and promote the early hydration reaction [21,22], improving the effect of the early mechanical properties of cementitious materials. palygorskite is mostly used in the construction field [23][24][25][26], but little research has been reported in the filling field.…”
Section: Introductionmentioning
confidence: 99%